2023
DOI: 10.1002/wps.21147
|View full text |Cite
|
Sign up to set email alerts
|

Transdiagnostic risk of mental disorders in offspring of affected parents: a meta‐analysis of family high‐risk and registry studies

Rudolf Uher,
Barbara Pavlova,
Joaquim Radua
et al.

Abstract: The offspring of parents with mental disorders are at increased risk for developing mental disorders themselves. The risk to offspring may extend transdiagnostically to disorders other than those present in the parents. The literature on this topic is vast but mixed. To inform targeted prevention and genetic counseling, we performed a comprehensive, PRISMA 2020‐compliant meta‐analysis. We systematically searched the literature published up to September 2022 to retrieve original family high‐risk and registry st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…We selected the 9 to 16 years age range to encompass youths who had not yet reached the typical age of depression onset ( 86 ). However, some studies have shown that high-risk youths may experience earlier onset of psychopathology than control offspring ( 36 , 38 ). By selecting asymptomatic youths, we might have missed some of the high-risk sample that had already developed depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected the 9 to 16 years age range to encompass youths who had not yet reached the typical age of depression onset ( 86 ). However, some studies have shown that high-risk youths may experience earlier onset of psychopathology than control offspring ( 36 , 38 ). By selecting asymptomatic youths, we might have missed some of the high-risk sample that had already developed depression.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of white matter integrity has also been observed in high-risk offspring in the cingulum, corpus callosum, and uncinate fasciculus, with reduced fractional anisotropy in the cingulum being related to elevated depression scores ( 34 , 35 ). Compared to the general population, high-risk youths have an increased probability of mood disorder onset due to their genetic and environmental relationships with family member(s) who have a severe mental disorder ( 36 , 37 , 38 ). Familial risk is known from birth or an early age, making it possible to study development in individuals who are at risk at a time when they have not experienced depression.…”
mentioning
confidence: 99%
“…Multicomponent and multilevel interventions should include informative campaigns for young people to be disseminated in schools, the promotion of antistigma campaigns through the use of social media on the importance of early referral to specialistic care and help-seeking [38], and the establishment of non-stigmatizing mental health care facilities dedicated to young people needs, in order to facilitate access and appropriate mental health care [39][40][41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents who grow up with a parent with a mental illness are a particularly vulnerable group to develop a mental disorder themselves ( 25 28 ). A recent large meta-analysis reported a lifetime risk of 55% among those children and adolescents to develop any mental disorder ( 27 ), whereby subclinical symptoms occur more often and earlier in life ( 29 ). Due to their close and dependent relationship to their parents, these children and adolescents are also considered to be particularly affected by SBA ( 21 , 30 ) and stigmatization has been identified as a potential social mechanism in the transgenerational transmission of mental disorders (TTMD) ( 29 ).…”
Section: Introductionmentioning
confidence: 99%